Special education past, present, and future perspectives from the field - Cook, Bryan G.; Tankersley, Melody; Landrum, Timothy J. (Bingley, U.K. : Emerald, 2014)
This volume explores serious challenging behavior in schools, with an emphasis on promising and research-based approaches to dealing with such behavior. Topics include what we know about (a) the nature and extent of the problem (e.g., rates of aggression, violence, and noncompliance in schools); (b) addressing extreme forms of noncompliance; (c) dealing with serious disruptive behavior; (d) violence prevention programs; (e) schoolwide response to aggression and violence; (f) issues of covert antisocial behavior (e.g., vandalism, truancy, theft); (g) functional behavioral assessment and function-based interventions; (h) legal and policy considerations in disciplining students with disabilities; and (i) promising and needed avenues for further research.
IDEA and learning disabilities : perspectives, problems, and proposals / Barbara Bateman -- Reflections on the concept of the least restrictive environment in special education / Jean B. Crockett -- Past, present, and future in EBD and special education / James M. Kauffman -- Students with learning and behavioral disabilities and the school-to-prison pipeline : how we got here, and what we might do about it / C. Michael Nelson -- Teaching students with emotional disabilities : challenges and opportunities / Robert A. Gable -- Design and management of scientific research in applied school settings / Hill M. Walker, Steven R. Forness, Kathleen Lynne Lane -- Reflections on progress monitoring and data-based intervention / Stanley l. Deno -- Learning in online environments : a new reality for students with disabilities / Diana Greer, Donald D. Deshler -- Special education in Norway : the past, present, and future of the field / Terje Ogden.
Print version record
Keywords: Education -- Teaching Methods & Materials -- General; Education -- General; Teaching of students with emotional & behavioural difficulties; Teaching skills & techniques; Education; Special education